UNDERSTANDING ENGLISH LANGUAGE DEMANDS AND CHALLENGES AMONG HEALTHCARE PROFESSIONALS IN BATAM: A TARGET SITUATION ANALYSIS - Hendra Nugraha; Muhammad Juliansyah Bedrio. D; Desty Febria (English Study Program University of Pasir Pengaraian, 2026)
English proficiency is increasingly important for medical personnel working in multilingual healthcare environments. This study examines the English language needs and challenges faced by medical staff in Batam, Indonesia, using a Target Situation Analysis (TSA) framework. A qualitative case study design was employed, with data collected through semi-structured interviews with ten medical staff members, including nurses and midwives, who had at least five years of hospital experience and prior experience communicating with foreign patients in English. Data were analyzed using thematic analysis. The findings reveal that English is primarily needed for communicating with foreign patients and for professional interactions. Speaking and listening were identified as the most essential skills, with pronunciation clarity playing a significant role in patient safety. However, participants reported several challenges, including limited medical vocabulary, grammar difficulties, listening comprehension problems, pronunciation issues, and low confidence when speaking English. The study concludes that a gap exists between workplace communication demands and medical staff's English proficiency. Therefore, TSA-based English for Medical Purposes (EMP) training is recommended to address practical communication needs in healthcare settings.